Alexinomia: The fear of using personal names - Ditye, Thomas; Rodax, Natalie; Welleschik, Lisa (Frontiers in Psychology, 2023)
Preliminary research based on everyday observations suggests that there are people, who experience severe fear when addressing others with their personal names. The aim of this study was to explore the extent to which this hitherto little-known psychological phenomenon really exists and to investigate its characteristic features, considering the everyday experience of not being able to use names and its impact on affected individuals and their social interactions and relationships. In this mixed-methods study based on semi-structured interviews and psychometric testing, 13 affected female participants were interviewed and evaluated using self-report measures of social anxiety, attachment-related vulnerability, and general personality traits. An inductive content analysis and inferential statistical methods were used to analyze qualitative and quantitative data, respectively. Our findings show that affected individuals experience psychological distress and a variety of negative emotions in situations in which addressing others with their name is intended, resulting in avoidance behavior, impaired social interactions, and a reduced quality of affected relationships. The behavior can affect all relationships and all forms of communication and is strongly linked to social anxiety and insecure attachment. We propose calling this phenomenon Alexinomia, meaning “no words for names”.